Kembara Kenali Borneo One Adventure Million Memories - Mimi Rabita, Abd Wahit (UMPSA, 2023)
KOTA KINABALU, 6 September 2023 - His Majesty the Yang di-Pertuan Agong Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah, who is also the Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), together with Her Majesty The Raja Permaisuri Agong Tunku Azizah Aminah Maimunah Iskandariah, was pleased to hold a Kembara Kenali Borneo tour in Sabah and Sarawak, starting from 3 to 13 September.